The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4252/wjsc.v11.i2.55
|View full text |Cite
|
Sign up to set email alerts
|

Rational use of mesenchymal stem cells in the treatment of autism spectrum disorders

Abstract: Autism and autism spectrum disorders (ASD) refer to a range of conditions characterized by impaired social and communication skills and repetitive behaviors caused by different combinations of genetic and environmental influences. Although the pathophysiology underlying ASD is still unclear, recent evidence suggests that immune dysregulation and neuroinflammation play a role in the etiology of ASD. In particular, there is direct evidence supporting a role for maternal immune activation during prenatal life in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 192 publications
0
8
0
Order By: Relevance
“…In particular, MSCs derived from the Wharton's jelly of umbilical cord tissue (UC-MSCs) may possess greater immune-modulatory activity [34] and proliferative capacity compared with other MSCs [35,36]. The rationale for MSC therapy to treat ASD has been discussed over the past decade [37,38]; our group proposed the use of stem cell therapy to treat ASD in 2007 [39]. Some studies to date have demonstrated the safety of treatment that included MSCs [40]: of note, the results of a study by Sharma et al showed that the majority (96%) of children with ASD treated with bone marrow-derived cells including MSCs showed global improvements including behavior patterns (66%), social relationships (90.6%), and speech, language, and communication (78%) [41].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MSCs derived from the Wharton's jelly of umbilical cord tissue (UC-MSCs) may possess greater immune-modulatory activity [34] and proliferative capacity compared with other MSCs [35,36]. The rationale for MSC therapy to treat ASD has been discussed over the past decade [37,38]; our group proposed the use of stem cell therapy to treat ASD in 2007 [39]. Some studies to date have demonstrated the safety of treatment that included MSCs [40]: of note, the results of a study by Sharma et al showed that the majority (96%) of children with ASD treated with bone marrow-derived cells including MSCs showed global improvements including behavior patterns (66%), social relationships (90.6%), and speech, language, and communication (78%) [41].…”
Section: Introductionmentioning
confidence: 99%
“…mediate diseases allied to inflammation and tissue damage such as ASD [32,33]. The specific relationship between this gene and the term autism which is predominantly a male disorder remains to be elucidated.…”
Section: Plos Onementioning
confidence: 99%
“…A cascade of events, leading disruption of neuronal maturation and dysfunctional networking through dysfunctional astrocytic neuronal support. A comprehensive review on this topic was recently published by Liu et al (25). More interestingly, neuropathological investigations have recently provided evidence in support of the inflammatory theory, describing perivascular lymphocytic infiltration in the cerebral white, gray matter, and neuronal leptomeninges, this infiltrates were quantitatively accompanied by a corresponding magnitude of astrocytic activation in the affected regions of the brain.…”
Section: Efficacy Of the Proceduresmentioning
confidence: 95%
“…Indeed, a recent proteomic analysis study discovered nine serum proteins to be significantly different in ASD compared to typically developing boys and a significant correlation with ASD severity according to ADOS (24). Possible mechanisms for the way stem cells improve autism have been discussed more extensively by Liu et al (25). In summary, two mechanisms seem to prevail: (a) reset of the immunological system and (b) improved vascular perfusion of the brain, two mechanisms that are addressed both by the stem cells but also by the bone marrow plasma, rich in growth hormones.…”
Section: Efficacy Of the Proceduresmentioning
confidence: 99%